The Effects of 12-week Online-delivered Isometric and Dynamic Core Stability Exercises on Functional Movement, Dynamic Postural Control, and Core Endurance in Healthy Young Adults - Namkuk Son; Hoyong Sung; Geonhui Kim; Harim Choe; Yeun Ryu; Yeonsoo Kim (Asian Society of Kinesiology, 2023)
OBJECTIVES The purpose of this study was to compare the effects of 12-week online-delivered isometric and dynamic core stability exercises on functional movements, dynamic postural control, and core endurance in healthy young adults. METHODS This is a single-blind randomized controlled trial. Sixty young adults (age range: 19-34 years; 12 males, 48 females) participated in this study. They were randomly assigned to the isometric core exercise [ICE], dynamic core exercise [DCE], or control group. Participants in the ICE and DCE groups performed 40-60 min real-time online-delivered core exercise session via Zoom video conferencing application, twice a week for 12 weeks. Participants in the control group did not participate in exercise intervention. All participants were asked not to participate in other exercises for 12 weeks. The outcome measurements include the functional movement screen, Y-balance test (upper & lower), and core endurance tests (flexor, extensor, and lateral flexor of the trunk). RESULTS The results of this study showed significant improvement in core endurance, functional movement, and dynamic postural control of the upper body in the ICT and DCE groups compared with the control group. However, significant differences were not found between the ICE and DCE groups in all variables. CONCLUSIONS Both types of online-delivered core exercise programs have been shown to be effective in improving functional movement, dynamic posture control, and core endurance in young adults. In addition, since both types of exercise have been shown to be effective on core stability related variables, both types of exercise can be recommended for young adults. However, further studies are warranted to investigate the gender differences on the effects of the core stability exercises.